Feasibility of PBL (Problem Based Learning)-based Sound Wave Electronic Student Worksheet for High School Students Using the Liveworksheet Application - Husnul Fuadi; Gunawan Gunawan; Susilawati Susilawati (Jurnal Penelitian Pendidikan IPA, 2022)
Digital teaching materials are one of the alternative solutions in the learning process in the era of digitalization 4.0. One of the digital teaching materials that can be developed in digital form is student worksheet. In addition to digital teaching materials, the selection and use of learning models is also important in supporting the learning process in schools. One of the learning models that can be used is the PBL (Problem Based Learning) learning model. This study aims to describe the feasibility of PBL-based sound wave electronic student worksheet digital teaching materials using the Liveworksheet application for high school students. This type of research is research and development (R&D) using the ADDIE model. The test subjects were students of class XI MIPA PC (Prima Cendekia) Senior High School of 3 Mataram. Data collection techniques through observation and distribution of questionnaires. The data obtained were analyzed qualitatively and quantitatively using quantitative descriptive statistics. The results showed that the PBL-based sound wave electronic student worksheet that had been developed obtained an assessment score from expert validation of 0.86 (very valid) with 90.6% reliability (reliable) and practitioner validation of 0.83 (very valid) with 95.55% reliability (reliable). Based on these results, it can be concluded that the PBL-based sound wave electronic student worksheet is proven valid so that it is suitable for use in the learning process in schools.